Teori konsep 'Keindahan' oleh Johann Joachim Winckelmann dalam kalangan pengkarya seni catatan landskap di Malaysia - Mohd Affwan Izam, bin Romli. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
'Beautification' in landscape painting has become a major question in Malaysia art scenario. The characteristic of 'beauty' is related with aesthetics that efers to natures or arts that have value according to the perception of an individual. This refers to beauty, attractiveness, amazing and fascinating. The perception of an individual able to refects and interpret an object as beautiful. The discovery of four theories by Johann Joachim Winckelmann is very significant should be analyzed nased on the landscape painter identify in Malaysia. According to Johann Joachim Winckelmann, the theory and concept of 'beauty' involves, 'beauty concept', 'beauty' in painting, evaluation of 'beauty' in arts, and how to evaluate 'beauty' in arts.